Religious diversity in science: Stereotypical and counter-stereotypical social identities. (October 2022) - Sharp, Carissa A.; Leicht, Carola; Rios, Kimberly; Zarzeczna, Natalia; Elsdon-Baker, Fern
Research shows that scientists tend to be less religious than the general population, and scientists' religious affiliation and participation have declined over time (Ecklund & Park, 2009; Ecklund et al., 2008). Given the demographic differences between scientists and the general population, it was predicted that scientists who are religious would be regarded as having a counter-stereotypical combination of social identities. However, across five studies, we found that people's own religious identities played a moderating role in the perception of a religious scientist. Although atheist participants perceived religious scientists as being more counter-stereotypical than atheist scientists, the same was not consistently found for nonreligious (but not atheist) or religious participants. These findings have important implications for debates around the underrepresentation of religious individuals in science. As religious individuals do not perceive these two identities to be incompatible, it may be stereotypes that others have about religious individuals and the culture of science more generally, rather than self-stereotypes, that are hurdles for religious individuals choosing a scientific career. Future research should take these findings into account and explore other potential barriers that lead to the underrepresentation of religious individuals within STEM fields.